2018
DOI: 10.1021/acsami.8b01737
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Dye-Sensitized Solar Cells Based on Colloid–Solution Deposition Planarized Fluorine-Doped Tin Oxide Substrates

Abstract: The transmittance and conductivity of fluorine-doped tin oxide (FTO) conductive glasses are the critical factors limiting the performance of dye-sensitized solar cells (DSSCs). Here, the transmittance and conductivity of commercial FTO glasses were improved via a colloid-solution deposition planarization (CSDP) process. The process includes two steps. First, the FTO nanocrystal colloid was deposited on the FTO glasses by spin-coating. Secondly, the coated glasses were treated by FTO precursor solution. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Here, a piece of FTO conducting glass deposited with a 350 nm-thick conductive film of fluorine-doped tin oxide was dipped into acetone and isopropanol successively for 30 min, then dried to serve as the front electrode. The surface of the FTO-glass is roughly textured ( Supplementary Figure 5A ), as a result of the low symmetric tetragonal crystal structures of fluorine-doped tin oxide ( Zhang et al, 2018 ). This structure is similar to the wrinkles on the surface of the bacterial plasma membrane, which facilitates attachment of the photosynthetic complexes ( Csiki et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, a piece of FTO conducting glass deposited with a 350 nm-thick conductive film of fluorine-doped tin oxide was dipped into acetone and isopropanol successively for 30 min, then dried to serve as the front electrode. The surface of the FTO-glass is roughly textured ( Supplementary Figure 5A ), as a result of the low symmetric tetragonal crystal structures of fluorine-doped tin oxide ( Zhang et al, 2018 ). This structure is similar to the wrinkles on the surface of the bacterial plasma membrane, which facilitates attachment of the photosynthetic complexes ( Csiki et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Attempts are being made to fabricate optical devices (TiO 2 , 41) amorphous Si, 42) fluorine-doped SnO 2 43) ) onto the planarization layer fabricated by a similar method. MgZnO/ ZnO films have been also fabricated on the SDP.…”
Section: Introductionmentioning
confidence: 99%
“…SnO 2 has a high photochemical property and stability, and is extensively studied in the fields of Li-ion batteries [ 29 , 30 , 31 ], dye sensitized solar cells [ 32 , 33 , 34 ], and gas sensors [ 35 , 36 , 37 ]. Additionally, many studies have shown that the SnO 2 /α-Fe 2 O 3 heterogeneous catalyst has an excellent photodegradation activity.…”
Section: Introductionmentioning
confidence: 99%